(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2010)
Phase relationships in the polyphosphate acids- containing melted systems of Ti–P2O5–Н2O, Ti2O3–P2O5–Н2O, TiN–P2O5–Н2O and with presents of alkali oxides (lithium, sodium and potassium) were investigated. Conditions of Ti(PO3)3 and TiP2O7 crystallization were identified. High stability of Ti (III) in melts of polyphosphate acids for temperature range of 350–600 °С was shown. Suitable pathway of Ti(PO3)3 preparation was proposed. UV/VIS, FTIR and EPR spectra of titanium (III) metaphosphate were discussed. The scheme of thermal decomposition of latter compound was determined on the basis of DTA data